Colorectal cancer mortality prevented by use and attributable to nonuse of colonoscopy - Stock, C.; Knudsen, A.; Lansdorp_Vogelaar, Iris; Haug, U.; Brenner, H. (Mosby Inc., 2011)
Background: Use of colonoscopy is thought to reduce colorectal cancer (CRC) mortality, but its impact at the population level is unclear. Objective: To estimate the effect of current colonoscopy use on CRC mortality and its further potential in reducing CRC mortality. Design: Population-level analysis was performed by using the concepts of prevented and attributable fractions, by using data from the National Health Interview Survey, the Surveillance, Epidemiology and End Results Program, and estimates of the effectiveness of colonoscopy at reducing CRC mortality. Setting: The 2005 U.S. population aged 50 years and older. Exposure: Colonoscopy within 10 years or less. Main Outcome Measurements: Percentages and absolute numbers of CRC deaths prevented and potentially preventable by colonoscopy. Limitations: Uncertainty in effectiveness estimates. Results: Overall, the proportions of CRC deaths in 2005 prevented by colonoscopy (ie, the prevented fractions) range from 13% (95% CI, 11%-15%) to 19% (95% CI, 12%-24%) across the estimates of colonoscopy effectiveness. Corresponding numbers of CRC deaths prevented range from 7314 (95% CI, 6010-8467) to 11,711 (95% CI, 7077-14,898). The proportions of CRC deaths attributable to nonuse of colonoscopy (ie, the attributable fractions) range from 28% (95% CI, 22%-33%) to 44% (95% CI, 24%-60%), depending on the assumed effectiveness. Corresponding numbers of CRC deaths attributed to nonuse of colonoscopy range from 13,796 (95% CI, 11,076-16,255) to 22,088 (95% CI, 12,189-29,947). Conclusions: Although we estimate that colonoscopy has prevented substantial numbers of CRC deaths, many more deaths could have been prevented with more widespread use. These findings highlight the potential benefits from public health interventions to increase the use of screening colonoscopy. © 2011 American Society for Gastrointestinal Endoscopy.